Choose and Play: Interactive to Facilitate Student Engagement in Basic Accounting Learning - Yola Firiana; Sri Sumaryati (Jurnal Media dan Teknologi Pendidikan, 2025)
Basic accounting learning found problems with student involvement both in terms of behavior, cognitive and affective aspects which were indicated by the attitude of not trying to do the assignments themselves but cheating on their friends and when discussing with their group team there were several passive students. The purpose of the study was to develop interactive multimedia Choose and Play Accounting to facilitate student involvement in Basic Accounting learning. The type of research used was R&D with the ADDIE model. This research was conducted in vocational school. The data collection technique used was distributing questionnaires. The results of the validity assessment from material experts were 49 (very good). The assessment from multimedia experts got 60 (very good). The assessment from language experts got 34 (very good). The validity assessment obtained from the material aspect teacher got 51 (very good), the multimedia aspect got 64 (very good), the language aspect got 35 (very good). The results of the trial followed by 14 students got a score of >18 with very good criteria. From the results it can be concluded that interactive multimedia Choose and Play Accounting is feasible to be used to facilitate student involvement, especially in basic accounting learning.